Comparative analysis of the open and the arthroscopic Latarjet procedure - M. L. Holovakha; O. V. Shchokin; B. A. Kuznietsov (Zaporožskij Medicinskij Žurnal)
Latarjet procedure is one of the relevant surgical techniques for the anterior and antero-inferior type of recurrent instability in the shoulder joint with a defect in the articular surface of the glenoid.